2010
DOI: 10.4314/pamj.v4i1.53613
|View full text |Cite
|
Sign up to set email alerts
|

Chronic suppurative otitis media: Socio-economic implications in a tertiary hospital in Northern Nigeria

Abstract: Background:In developing countries, ear infections and deafness are usually neglected conditions due to insufficient funds, work force, facilities, and knowledge. This paper highlights the socio-economic burden of chronic suppurative otitis media on a northern Nigerian population with suggestions on ways to reduce this burden.Method:Seventy-four patients presenting to the Otorhinolaryngology unit, Department of surgery, Jos University Teaching Hospital, Plateau state, Nigeria with chronic suppurative otitis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 8 publications
3
58
0
5
Order By: Relevance
“…[4,5,[14][15][16] The predominance of unilateral disease in children with CSOM has previously been noted. [3,12,[16][17][18][19] Most children who had been treated prior to referral did not respond to the treatment given or relapsed, which was the reason for referral.…”
Section: Discussionmentioning
confidence: 68%
“…[4,5,[14][15][16] The predominance of unilateral disease in children with CSOM has previously been noted. [3,12,[16][17][18][19] Most children who had been treated prior to referral did not respond to the treatment given or relapsed, which was the reason for referral.…”
Section: Discussionmentioning
confidence: 68%
“…[18] The complications of CSOM in this study also differ from those of Adoga where complications of CSOM were mastoid abscess (6.8%), subperiosteal abscess (1.4%), meningitis (1.4%) and facial nerve paralysis (1.4%). [24] However we cannot establish the explanation for this difference. Our overall mortality of 4.5% is higher than Mostafa's and Yagizy's mortality of 1.42% and 2.4% respectively.…”
Section: Discussionmentioning
confidence: 85%
“…This is in contrast to other studies that found a male predominance. [19][20][21][22][23] While a national study on hearing in the United Kingdom found no gender difference. 24 Many investigators have revealed the role of upper respiratory tract abnormalities as causative factors for ET obstruction in the etiopathogenesis of COM.…”
Section: Discussionmentioning
confidence: 99%